Comparative Advantage Of Malaysian Manufacturing Industry - Tan, Jee Ching (2005)
Changes in comparative advantage should reflect changes in factor endowment. Increasingly changes in trade policies also affect a country's trade performance. The competitiveness status of manufacturing industries for malaysia is determined in this study using the Revealed Comparative Advantage method of Balassa.